Pengaruh Gaya Kepemimpinan, Komunikasi, Pembagian Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Pt.Telkom surakarta( Studi Kasus Pada Kantor PT.Telkom Surakarta) - Daningrum, Lusi Ermin; , Drs. Suyatmin Waskito Adi, M.Si (2016)
Employee performance is an important factor in the company, because it can determine the company's success. Leadership styles can affect every employee in a company. Good communication can enhance good relations between colleagues. The combination between an appropriate division of labour or the right person at the righ place and the style of leadership, communication and work discipline can produce a good performance for the company's employees. The purpose of this study is to determine the effect of leadership styles, communication, division of labou, and work discipline on the performance of employees at PT. Telkom Surakarta partially or simultaneously. The population of the research was all employee of PT.Telkom Surakarta with total of 185 staff, and the samples of the research were 65 staff. The research method using multiple regression analysis. The result of this study is the style of leadership, communication, division of labour, and work dicipline have a positive and significant effect either simultaneously or partially on employee performance.